The College [Codrington College], Barbados - (:unkn) unknown (My University, 2022)
A view of The College [Codrington College], Barbados showing a line of palm trees adjacent to the building, near a pond. There is a man on horseback on the grounds near the pond. At the back of the photograph the following is written in pencil - £35.
Landscape; Black & white; 3 1/2 x 2 1/2 inches
Keywords: Clergy; Historic buildings; Historic sites; Religious education; Theological seminaries; Universities and colleges; Architectural elements; Lakes and ponds; Palms; Codrington College